The effect of NF-kB and MAPK mediated Proinflammatory microenvironment on renal aging and amyloid deposition in elder rats - Mete Keçeci; Cenk Murat Özer; Esra Babaoğlu; Furkan Bodur; Ali Can Önal; Ayşe Zeynep Yılmazer Kayatekin; Osman Cengil; Ali Serdar Karataş (Scientific Reports)
Abstract Low-grade inflammation associated with the aging process exerts functional and morphological effects on multiple organs. The kidney is an organ that is severely affected by the aging process. Our study aimed to determine the relationship between histopathological and immunohistochemical changes and age-related amyloid accumulation in rat kidney tissue. Wistar albino rats were divided into two groups: young adult and elder (n = 8, 24 and 104 weeks old, respectively). H&E, PAS, and Congo red staining and immunohistochemical staining for TNF-α, IL-6, occludin, GRP78, and mitogen-activated protein kinase (MAPK) were performed on the kidney tissues of the subjects. A significant difference was found between the groups in terms of glomerulus diameter/Bowman’s capsule diameter, percentage of sclerotic glomeruli, epithelial desquamation, loss of brush border, casts, tubular dilatation, cellular debris, and the presence of apoptotic cells. TNF-α, IL-6, GRP78, and MAPK protein levels were shown to increase significantly in aged rat kidneys, whereas occludin levels decreased significantly. No amyloid accumulation was found in the kidney, heart, skin, and small intestine tissues of either group. The results of our study suggest that the proinflammatory microenvironment required for AA amyloid deposition in systemic amyloidosis induced by low-grade inflammation in old age cannot be generated by the action of NF-κB, MAPK, and MAPK-activated JNK and AP-1 transcription factors alone.